Clinical introduction of Monte Carlo treatment planning for lung stereotactic body radiotherapy. (6th January 2014) - Miura, Hideharu; Masai, Norihisa; Oh, Ryoong–Jin; Shiomi, Hiroya; Yamada, Kouichi; Sasaki, Junichi; Inoue, Toshihiko
Abstract : The purpose of this study was to investigate the impact of Monte Carlo (MC) calculations and optimized dose definitions in stereotactic body radiotherapy (SBRT) for lung cancer patients. We used a retrospective patient review and basic virtual phantom to determine dose prescriptions. Fifty‐three patients underwent SBRT. A basic virtual phantom had a gross tumor volume (GTV) of 10.0 mm with equivalent water density of 1.0 g/cm 3, which was surrounded by equivalent lung surrounding the GTV of 0.25 g/cm 3 . D95 of the planning target volume (PTV) and D99 of the GTV were evaluated with different GTV sizes (5.0 to 30.0 mm) and different lung densities (0.05 to 0.45 g/cm 3 ). Prescribed dose was defined as 95% of the PTV should receive 100% of the dose (48 Gy/4 fractions) using pencil beam (PB) calculation and recalculated using MC calculation. In the patient study, average doses to the D95 of the PTV and D99 of the GTV using the MC calculation plan were 19.9% and 10.2% lower than those by the PB calculation plan, respectively. In the phantom study, decreased doses to the D95 of the PTV and D99 of the GTV using the MC calculation plan were accompanied with changes GTV size from 30.0 to 5.0 mm, which was decreased from 8.4% to 19.6% for the PTV and from 17.4% to 27.5% for the GTV Similar results were seen with changes in lung density from 0. 45 to 0.05 g/cm 3, with doses to the D95 of the PTV and D99 of the GTV were decreased from 12.8% to 59.0% and from 7.6% to 44.8%, respectively. The decrease in dose to the PTV with MC calculation was strongly dependent on lung density. We suggest that dose definition to the GTV for lung cancer SBRT be optimized using MC calculation. Our current clinical protocol for lung SBRT is based on a prescribed dose of 44 Gy in 4 fractions to the GTV using MC calculation. PACS number: 87.55.D‐, 87.55.K‐